Sadie's secret [large type] - Y'Barbo, Kathleen (Y'Barbo, Kathleen. Secret lives of Will Tucker, 2015)
Louisiana, 1890--Sarah Louise "Sadie" Callum is a master of disguise, mostly due to her training as a Pinkerton agent but also from evading overprotective brothers as she grew up. When she takes on a new assignment with international connections, she has no idea her new cover will lead her on the adventure of a lifetime.